Introduction (The Poet and his world) - Quayum, Mohammad Abdul (Orient BlackSwan (Orient Longman), 2011)
The volume has eminent scholars like, Sukanta Chaudhuri, Bharati Ray, William Radice, Uma Dasgupta, Abhijit Sen and others as contributors.